Numerical solutions and comparisons for nonlinear time fractional ito coupled system - Aslan, Ebru Cavlak; İnç, Mustafa (American Scientific Publishers, 2016)
In this paper, the homotopy analysis method (HAM) are implemented to time fractional Ito coupled system (FIcS). The fractional derivatives are described Caputo sense. A comparison was also made between homotopy perturbation method (HPM) and HAM and the results show that the method is very effective. We also give a convergence theorem for time fractional Ito coupled system. © Copyright 2016 American Scientific Publishers All rights reserved.
Keywords: Fractional calculus; Fractional ito coupled system; Homotopy analysis method (ham)